Legal Awareness of Online Motorcycle Taxi Drivers “Gojek” Related to Their Participation in the Workplace Accident Insurance and Death Insurance Program in Surabaya City - Kamila Fakhriyah Aris; Mahendra Wardhana; Ibtisam Mumtaz Khairunnisa (NOVUM : JURNAL HUKUM, 2024)
The BPJS Law in article 14 states, "every person, including foreigners who have worked for a minimum of 6 (six) months in Indonesia, is obliged to become a participant in the Social Security program".  The partnership relationship means that there is no obligation for application companies to register their drivers with BPJS Employment. Therefore, work partners at the Gojek company must register themselves as BPJS participants independently. According to the Minister of Manpower Regulation Number 5 of 2021 in Article 32, it is stated that non-wage earners are required to take part in 2 programs, namely work accident insurance and death insurance. This research aims to find out the legal awareness of online motorcycle taxi drivers regarding their participation in work accident insurance and death insurance in the city of Surabaya. To achieve this goal, this research will use empirical legal research and an empirical juridical approach or legal sociology. The research results show that there are four indicators that can be used to measure the level of public legal awareness, including legal knowledge, legal understanding, legal attitudes, and legal behavior patterns. Each indicator shows a certain level of legal awareness, ranging from whether it is low or high. Based on the research results, Gojek online motorcycle taxi drivers in Surabaya who became informants were divided into those with very high legal awareness and those with moderate legal awareness. The level of legal awareness of Gojek online motorcycle taxi drivers is influenced by several factors.